Implementasi Corporate Social Responsibility (CSR) pada Perusahaan Daerah Air Minum (PDAM) Surya Sembada Kota Surabaya (Studi Kasus Pembangunan Jamban Sehat dan Pembangunan Rumah Tidak Layak Huni) - Reviandani, Oktarizka (Jurnal Bisnis Indonesia, 2024)
Corporate Social Responsibility (CSR) is one of the actions carried out by companies as a form oftheir responsibility towards the environment around which the company is located is at. One of theCorporate Social Responsibility (CSR) programs currently being implemented by PDAM SuryaSembada Kota Surabaya is the Healthy Latrines and Renovating Uninhabitable Houses Program.This program is a program of the Mayor of Surabaya in collaboration with PDAM and the SurabayaCity National Zakat Amil Agency (BAZNAS). Through this program, PDAM together with BAZNASwill build 20 houses and will build 20 healthy latrines in various areas in Surabaya. This researchaims to describe the implementation of CSR at PDAM Surya Sembada Surabaya City in the form ofbuilding healthy latrines and building uninhabitable houses. The research method used is descriptivewith a qualitative approach. The focus of this research consists of 1) Communication, 2) BureaucraticStructure, 3) Disposition and 4) Resources. The data collection techniques used are documentation,observation and interviews. Data analysis was carried out by collecting data, reducing data,presenting data, and drawing conclusions. The results of this research show that the RegionalDrinking Water Company, Surya Sembada, Surabaya City has implemented the Healthy Latrines andUninhabitable House Renovation Program well, but the process of disbursing CSR funds is often late.The advice given in this research is that PDAM Surya Sembada Surabaya City needs to speed up theprocess of disbursing funds, and continue the program of building healthy latrines and renovatinguninhabitable houses so that it doesn't stop here and can build healthy latrines for the public.Keywords: Implementation; Corporate Social Resposibility (CSR); PDAM Surabaya